The relationship between knowledge acquisition on international assignments and career development: an exploratory study with portuguese repatriates - Martins, Dora (2016)
This paper explores the relationship between the expatriates’ knowledge acquisition (KA) and their career development after an international assignment (IA). The purpose of this paper is to examine the role of expatriates in KA and transfer within International Portuguese multinational corporations. Furthermore, with this empirical study we try to analyse how the knowledge that is acquired and transferred translates into a basis for career development after the IA. This phenomenon has a special relevance in the Portuguese context, because this country is known a growing process of globalization in recent years. Furthermore, (a) there are no empirical studies concerning knowledge transfer and career development of repatriates from Portuguese companies; (b) little is known about the repatriates’ contributions to their home company after IA. This paper is one of the first to focus specifically on the repatriates’ role in KA and transfer from the host company to their Portuguese home company. A qualitative research methodology is used, specifically through an exploratory case study approach, which examines how knowledge management (KM) acquisition or transferring during IA are important for the repatriates’ career development in the Portuguese home company. Data were collected through semi-structured interviews to 42 Portuguese international assignees and 18 organizational representatives from nine Portuguese companies. Preliminary results show that KA and transfer made by Portuguese expatriates contributes directly to their career development. Moreover, evidence reveals that not all repatriates were promoted after their IA; rather some repatriates were even demoted after their IA. Furthermore, the results obtained suggest that the type of knowledge which acquired or transferred plays a central role in the career development after repatriation. According to these results, the paper discusses the major theoretical and practical implications. Suggestions for future research are also presented.